LARVAL PARASITOID COMPLEX ASSOCIATED WITH GRAM POD BORER, HELICOVERPA ARMIGERA (HUBNER) IN CHICKPEACROP ECOSYSTEM - BOHRIA, A.K.; SHUKLA, ABHISHEK; KUMAR, SANJAY (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2011)
Four parasitoids, Campoletis chlorideae (Uchida), Eriborus argenteopilosus (Cameron), Chelonus sp. and an unidentified tachinid fly were recorded parasitizing Helicoverpa armigera under chickpea crop ecosystem at five locations viz. Kewlari, Hatna, Khiriya, Piparia and Gurgawan in Jabalpur (M.P.) during Rabi 2001-02 and 2002-03. Out of which C. chlorideae was predominant and the activities of other three parasitoids were very low and that for a limited period. Fluctuations in parasitization level ranged from 8 to 54% at different locations. Most favourable period for the parasitization was second week of December to first week of January. Two hyper parasitoids of C. chlorideae namely, Brachymeria sp. and Philofena campoletisa (Narendran) were also observed.